2019
DOI: 10.1063/1.5084752
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric control of resistance switching in VO2/Pb(Zr0.52Ti0.48)O3 heterostructure

Abstract: The VO2/Pb(Zr0.52Ti0.48)O3 (PZT) thin film heterostructure device was first grown to investigate the piezoelectric control of resistance switching in Vanadium dioxide (VO2) films with a PZT underlayer. The results show that upon applying a continuous gate-electric-field (Eb) on the heterostructure, a butterfly shape resistance (R) vs. Eb curve of VO2 was observed. This R-Eb curve agrees well with the strain vs. electric-field “butterfly” curve of the underlying PZT, indicating that the resistance changes in VO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The VO 2 /ferroelectric heterojunctions have been fabricated and different polarization states in ferroelectrics can be tuned through the electric field. Therefore, different strain states are induced at the interface of VO 2 /ferroelectric and the multiresistance state of VO 2 is realized [144][145][146]. The MIT behavior of VO 2 is sensitive to the strain effect so that multi-resistance states are obtained.…”
Section: Field-effect Transistor (Fet)mentioning
confidence: 99%
See 1 more Smart Citation
“…The VO 2 /ferroelectric heterojunctions have been fabricated and different polarization states in ferroelectrics can be tuned through the electric field. Therefore, different strain states are induced at the interface of VO 2 /ferroelectric and the multiresistance state of VO 2 is realized [144][145][146]. The MIT behavior of VO 2 is sensitive to the strain effect so that multi-resistance states are obtained.…”
Section: Field-effect Transistor (Fet)mentioning
confidence: 99%
“…These properties of VO 2 make it have a potential application in strain sensors (detailed in the next section). Zhang et al [145] reported a VO 2 /ferroelectric thin film heterostructure device and investigated the piezoelectric control of resistance switching in a VO 2 thin film, as the device shown in the inset of Figure 20a. Under the electric field, the piezoelectric effect of ferroelectric thin film introduces the lattice strain at the interface of a VO 2 /ferroelectric thin film, and leads to the reversible resistance change of VO 2 .…”
Section: Field-effect Transistor (Fet)mentioning
confidence: 99%
“…But it can be seen that the result of the modulation is not very ideal. Zhang et al reported the piezoelectric control of resistance switching in the VO 2 film with the PZT underlayer, upon applying a gate-electric-field E b on the heterostructure, a butterfly shape resistance (R) vs. E b curve of VO 2 was observed [15]. The metal-insulator transitions can also be modified via the biaxial strain induced by the lattice mismatch with the substrate [5].…”
Section: Introductionmentioning
confidence: 99%
“…Still, there are several ways to modulate the strain of a thin film in situ. Attempts have been made to control the strain of thin films using piezoelectric materials [16][17][18][19][20][21][22][23][24][25][26]. They include some studies on the modification of the magnetic properties of (La, Sr)MnO 3 [16][17][18], CoFeB [19], and Ni [20] films, as well as some on the modification of the transition properties of VO x films [22][23][24][25][26], all grown on piezo layers or piezo substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to control the strain of thin films using piezoelectric materials [16][17][18][19][20][21][22][23][24][25][26]. They include some studies on the modification of the magnetic properties of (La, Sr)MnO 3 [16][17][18], CoFeB [19], and Ni [20] films, as well as some on the modification of the transition properties of VO x films [22][23][24][25][26], all grown on piezo layers or piezo substrates. It has been reported that the T tr of VO 2 films can be controlled through the strain of (1−x)Pb(Mg 1/3 Nb 2/3 )-xPbTiO 3 (PMN-PT) crystalline substrates by 1.35 • C [23] or by 6 • C [24].…”
Section: Introductionmentioning
confidence: 99%